Alterity and empathy: new paradigms to the humanities in the 21st century? - Diniz, Fábio Gerônimo Mota (Faculdade de Ciências e Letras - Unesp - Araraquara., 2015)
The text is intended to be a brief essay adressing the role of the scholar of the so called Human Sciences, under the light of the dilemmas brought by the contemporaneity, especially those who tend to deauthorize the humanistic role of the university and to open space to violent speeches, associated to the conservative mercantilist thought and to various types of prejudice. Facing the questioning of its importance in the present context, we believe that to the Humanities urges the clear delimitation of some premises that can guide its work, historically constituted under the light of the human rights. So, our proposal is a presentation of two paradigms which we believe are intrinsic to the humanist’s work, alterity and empathy, and that can be useful as foundations to a reflection about the work of the Human Sciences. Starting from these perspectives, we intend to confront these paradigms with the growing of the violent market speech, especially with the expansion of the world wide web and, consequently, of the virtual vehicles of information, that popularized very much these speeches in the last decade.